Peningkatan Kualitas Pendidikan melalui Seleksi dan Pelatihan Pengawas Sekolah (Pengalaman Kabupaten Sikka) - Ikhfan Haris (Jurnal Pendidikan dan Kebudayaan, 2014)
This paper deals with good practice which related to transparent and accountableÂ practices in the implementation of education. Good practice emerged as a response to the needÂ of a recruitment process, which should be based on an objective, transparent, fair and accountableÂ process, where quality of skill should also be taken into consideration in order to recruit theÂ right person who has the best skill in implementing educational supervision activities. The paperÂ aimed to review the implementation of a system innovation of educational supervision inÂ Kabupaten Sikka. This system covers supervisor recruitment process, training, institutionalÂ strengthening, and mechanism implementation. A series of good practices have been achievedÂ through this innovation,, e.g. standardisation of the supervision mechanism; an effective workingÂ time of supervisors; structured schedule for visiting schools and administration work; as well asÂ a clear division and assignment of volume and type of supervision that will be implemented byÂ supervisors. In addition, the strengthening of gender aspect that encouraging female teachers/principals to join the supervisor selection has become a new trend as well as a form ofÂ appreciation. It also provides equal opportunity for male and female teachers/principals toÂ compete fairly in the school supervisor selection.Â ABSTRAKArtikel ini merupakan good practice yang terkait dengan praktik-praktik transparansiÂ dan akuntabiltas dalam pelaksanaan kegiatan pendidikan. Gagasan ini muncul sebagai responÂ terhadap kebutuhan akan proses seleksi/rekruitmen pengawas yang dilandaskan pada prinsip prinsipÂ obyektif,Â transparan,Â fair,Â akuntabelÂ danÂ berdasarkanÂ pertimbangan kualitasÂ kemampuan,Â dalam rangka mendapatkan figur yang tepat dalam arti memiliki keahlian terbaik untuk melaksanakan kegiatan kepengawasan pendidikan. Tujuan kajian ini adalah melakukan reviewÂ terhadap hasil inovasi sistem kepengawasan pendidikan yang dikembangkan oleh DinasÂ Pendidikan dan Kebudayaan Kabupaten Sikka. Inovasi ini mencakup kegiatan seleksi/rekruitmen,Â pelatihan serta penguatan kelembagaan dan mekanisme kepengawasan pendidikan. Hasil kajianÂ menunjukkan bahwa sejumlah perubahan telah dicapai melalui inovasi ini, antara lainÂ terpenuhinya kebutuhan tenaga pengawas; standarisasi mekanisme pertanggungjawabanÂ kegiatan kepengawasan dan efektifnya penggunaan waktu dan struktur kerja pengawas,Â kejelasan pembagian dan penentuan volume dan jenis supervisi yang dilaksanakan olehÂ pengawas. Selain itu, penguataan aspek jender mendorong para guru/kepala sekolah perempuanÂ mengikuti seleksi pengawas menjadi â€œtrendâ€ baru, sebagai bentuk apresiasi pemberian peluang yang sama antara guru/kepala sekolah perempuan dan laki-laki berkompetisi secara sehatÂ dalam seleksi pengawas sekolah.